Experiences of violence during the COVID-19 pandemic among people who use drugs in a Canadian setting: a gender-based cross-sectional study - Anmol Swaich; Lindsey Richardson; Zishan Cui; Kora DeBeck; M-J Milloy; Thomas Kerr; Kanna Hayashi (BMC, 2023)
Abstract Objectives People who use drugs (PWUD) experience disproportionately high rates of violent victimization. Emerging research has demonstrated that the COVID-19 pandemic has exacerbated violence against some priority populations (e.g., women), however there is limited research examining the impact of the pandemic on the experiences of violence of PWUD. Methods Using data collected between July and November 2020 from three prospective cohort studies of PWUD in Vancouver, Canada, we employed multivariable logistic regression stratified by gender to identify factors associated with recent experiences of violence, including the receipt of COVID-19 emergency income support. Results In total, 77 (17.3%) of 446 men, and 54 (18.8%) of 288 women experienced violence in the previous six months. Further, 33% of men and 48% of women who experienced violence reported that their experience of violence was intensified since the COVID-19 pandemic began. In the multivariable analyses, sex work (Adjusted Odds Ratio [AOR] = 2.15, 95% confidence interval [CI]: 1.06-4.35) and moderate to severe anxiety or depression (AOR = 3.00, 95% CI: 1.37-6.57) were associated with experiencing violence among women. Among men, drug dealing (AOR = 1.93, 95%CI: 1.10-3.38), street-based income sources (AOR = 1.93, 95%CI: 1.10-3.38), homelessness (AOR = 2.54, 95%CI: 1.40-4.62), and regular employment (AOR = 2.97, 95% CI: 1.75-5.04) were associated with experiencing violence. Conclusion Our study results suggest economic conditions and gender were major factors associated with experiencing violence among our sample of PWUD during COVID-19. These findings highlight criminalization of drug use and widespread socioeconomic challenges as barriers to addressing violence among PWUD during periods of crisis.